2022
DOI: 10.31933/dijms.v3i3.1092
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Transformational Leadership Style, Workload and Job Satisfaction on Turnover Intention

Abstract: This study aims to analyze the transformational leadership style, workload and job satisfaction that effect employee turnover intention. The population of this study is employees at PT Dhanistha Surya Nusantara located in DKI Jakarta, with a sample of 117 workers whose determination is based on the use of the slovin formula. The data analysis method used the SPSS (Statistical Package for the Social Sciences) application. The result of the study is that transformational leadership has a significant negative imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
2
1
0
Order By: Relevance
“…Current study showed that the supervision was also affect job satisfaction. Although satisfaction with pay and benefits influenced turnover intention in addition to supervision ( (Situmorang & Wardhani, 2022). The results of this study confirmed the results of previous studies that have consistently shown a relationship between job satisfaction and their intention to leave their current workplace (Pratama, Suwarni, & Handayani, 2022).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Current study showed that the supervision was also affect job satisfaction. Although satisfaction with pay and benefits influenced turnover intention in addition to supervision ( (Situmorang & Wardhani, 2022). The results of this study confirmed the results of previous studies that have consistently shown a relationship between job satisfaction and their intention to leave their current workplace (Pratama, Suwarni, & Handayani, 2022).…”
Section: Discussionsupporting
confidence: 87%
“…The current finding indicated that employee are least satisfied with salary and benefits the finding is consistent with (Kuo, Lin, & Li, 2014;Situmorang & Wardhani, 2022) . Salary was the dominant factor for determining the level of job satisfaction, intention to leave and consideration of returning (Mawardi, 2022;Pratama, Suwarni, & Handayani, 2022;Chavadi, Sirothiya, & MR, 2022).…”
Section: Discussionsupporting
confidence: 81%
“…Employee resignation is a behavior shown by employees with the intention of wanting to change jobs or quit their current job in a company at the will ofsendir i (Widayati, Widjaja, & D, 2019). Employee resignation is a sense of wanting to transfer an employee's work from the previous company to another company with a specific purpose (Situmorang & Wardhani, 2022). Employee resignation is the desire of an employee to stop working at the company where they work due to certain factors such as: workplace situation, environment and workload (R. Sari, Hairul, & Wicaksono, 2021).…”
Section: Literature Review Employee Resignmentioning
confidence: 99%
“…The explanation above shows how dizzy the organization's commitment to an educational institution is. This study examines how the relationship between the locus of control and supervision variable indicators affects teacher organizational commitment [33]. The unit of analysis of this research is a public junior high school teacher in Tangerang Regency, Banten Province.…”
Section: Introductionmentioning
confidence: 99%